2018
DOI: 10.1080/15389588.2017.1403017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of morphological variations on cervical spine segmental responses from inertial loading

Abstract: Shape variations in the intervertebral disc influenced segmental rotation and ligament responses; however, the influence of shape variations in the facet joint was confined to capsular ligament responses. Response angle was most influenced by the vertebral body depth variations, explaining greater segmental rotations in female spines. Straighter spine segments sustained greater posterior facet joint compression, which may offer an explanation for the higher incidence of whiplash-associated disorders among fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Advances in computational power have expedited the FE model development process, and patient-specific FE models have emerged that incorporate the unique anatomical features of each patient [ 9 , 26 - 28 ]. In principle, patient-specific models will account for sex-specific morphological differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in computational power have expedited the FE model development process, and patient-specific FE models have emerged that incorporate the unique anatomical features of each patient [ 9 , 26 - 28 ]. In principle, patient-specific models will account for sex-specific morphological differences.…”
Section: Discussionmentioning
confidence: 99%
“…Consequent to their smaller size, female cervical vertebrae have smaller intersegmental contact areas as compared to males, which is predicted to result in less intrinsic stability and greater motion in response to force [1][2]. Indeed, John et al demonstrated segmental spinal motion is significantly influenced by variations in vertebral body size, specifically vertebral body depth [9]. Consistent with these observations and predictions, some [18][19] but not all [20] studies report the range of voluntary cervical spine motion is greater in females than males, even though voluntary neck muscle strength is significantly less in females [3,21].…”
Section: Sex-specific Intubation Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 41 42 ] The present model was developed using multiblock technique. [ 43 44 ] The differentiation of the vertebrae into different blocks allows the user to independently control the regional anatomy of the spine, thus achieving the patient-specific spine model using the baseline finite-element model. It should be noted that the baseline model was used for the current analysis of ROMs and osteophytes were not included.…”
Section: Discussionmentioning
confidence: 99%
“…( 2017 ) Frictionless Linear elastic: , = 0.4 John et al. ( 2018 ) Linear elastic: , = 0.3 Kang et al. ( 2010 ) Linear elastic: , = 0.45 Lee et al.…”
Section: Methodologies For Facet Joints Modelsmentioning
confidence: 99%